A seamless ubiquitous emergency medical service for crisis situations. Issue 126 (April 2016) - Lin, Bor-Shing
Highlights: In emergency and crisis situations, many communication channels can be unserviceable because of damage to equipment or loss of power. Thus, data transmission over wireless communication to achieve uninterrupted network services is a major obstacle. The proposed middleware can sense its operating environment and optimize the spectrum usage to integrate the existing heterogeneous wireless communication systems. The proposed middleware was ported into an embedded system, which is compatible with the actual network environment without the need for changing the original system architecture. Abstract: In crisis situations, a seamless ubiquitous communication is necessary to provide emergency medical service to save people's lives. An excellent prehospital emergency medicine provides immediate medical care to increase the survival rate of patients. On their way to the hospital, ambulance personnel must transmit real-time and uninterrupted patient information to the hospital to apprise the physician of the situation and provide options to the ambulance personnel. In emergency and crisis situations, many communication channels can be unserviceable because of damage to equipment or loss of power. Thus, data transmission over wireless communication to achieve uninterrupted network services is a major obstacle. This study proposes a mobile middleware for cognitive radio (CR) for improving the wireless communication link. CRs can sense their operating environment and optimize the spectrum usage so that the mobile middleware can integrate the existing wireless communication systems with a seamless communication service in heterogeneous network environments. Eventually, the proposed seamless mobile communication middleware was ported into an embedded system, which is compatible with the actual network environment without the need for changing the original system architecture.